Lyrics in The Dolalak Dance Purworejo Central Java as a Form of Islamic Folk Songs - Santosa, Djarot Heru; Haryono, Timbul; Soedarsono, RM (Center for Research and Development of Religious Literature and Heritage, 2013)
Dolalak dance is highly dependent on the power of the song lyrics, so it can be called a lyrical dance. The dancers will not be able to do perfect dance moventents only by musical accompaniment; the displacement and combination of dance movements are characterized by lyrics that accompany the songs. Thus, song lyrics have a very dominant role in the arrangement of the dance movements. Dolalak dance has approximately 64 types of movements. A one-night staging, as an illustration, usually begins with 13 types of movements, followed by a trance dance, and ends with 7 types of movements as the closing. Song lyrics in the Dolalak dance are mostly influenced by the nuances of Islamic teachings. This is proven by the presence of a lot of words and/ or terms in the song lyrics which are very close to the. Arabic words in Islamic teachings. More interestingly, as a form of folk songs used in the performance of traditional Javanese arts, the Arabic words are widely adapted to the speech or pronunciation of the local language, especially the Javanese one. As a result, the origin and meaning of certain words or terms in the lyrics are difficult to trace. However, it is understandable since sometimes words in the song lyrics are preferred to adjust particular sounds.